1987
DOI: 10.1093/nar/15.12.4737
|View full text |Cite
|
Sign up to set email alerts
|

Precursor-product relationship between vitellogenin and the yolk proteins as derived from the complete sequence of aXenopusvitellogenin gene

Abstract: In Xenopus laevis four estrogen-responsive genes are expressed simultaneously to produce vitellogenin, the precursor of the yolk proteins. One of these four genes, the gene A2, was sequenced completely, as well as cDNAs representing 75% of the coding region of the gene. From this data the exon-intron structure of the gene was established, revealing 35 exons that give a transcript of 5,619 bp without the poly A-tail. This A2 transcript encodes a vitellogenin of 1,807 amino acids, whose structure is discussed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 45 publications
(47 reference statements)
3
61
0
1
Order By: Relevance
“…Two N-glycosylation sites were found in the deduced amino acid sequence of the cloned cDNA. One set of 11 and two sets of 25 sequential serine residues are present in a molecular analysis of Xenopus phosvitin [13]. C. picta phosvitin also contains a high serine content; 50% of the total amino acid residues were serine [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two N-glycosylation sites were found in the deduced amino acid sequence of the cloned cDNA. One set of 11 and two sets of 25 sequential serine residues are present in a molecular analysis of Xenopus phosvitin [13]. C. picta phosvitin also contains a high serine content; 50% of the total amino acid residues were serine [19].…”
Section: Discussionmentioning
confidence: 99%
“…The C. picta lipovitellin is composed of two major subunits, with a molecular weight of 85 and 120 kDa [19]. The phosvitin of Xenopus possessed a high serine content [13]. In 1980, Ho et al reported that 50% of the total amino acids in C. picta phosvitin were serine [19].…”
mentioning
confidence: 99%
“…This putative region contains not only the serine clusters observed in phosvitin and phosvette I, but also the sequence characteristic of the amino terminus of lipovitellin 2␣ (Fig. 2;Gerber-Huber et al 1987;Wallace et al 1990). It is well known that yolk proteins such as phosvitin and lipovitellin are generated from their precursor protein vitellogenin.…”
Section: Discussionmentioning
confidence: 99%
“…We purified two BMP-binding proteins and identified them as lipovitellin 1 and Ep45, respectively, using their N-terminal amino acid sequences and biochemical analyses. Lipovitellin 1, which is processed from vitellogenin, is a 120-kDa yolk platelet protein (20,21). The precursor protein vitellogenin (210 kDa) is synthesized under estrogen control in the liver, transported to the ovary, and processed there to the yolk proteins lipovitellin and phosvitin (20,22).…”
mentioning
confidence: 99%